Pengembangan Media Pembelajaran Berbasis Android pada Materi Suku Banyak (Polinomial) - Zulinda Nur Saidah; Dewi Hamidah; Ahmad Syamsudin (Jurnal Tadris Matematika, 2022)
This study aims to develop android-based mathematics learning media on polynomial material that is valid, practical, and effective for use in learning. This type of research is research and development by applying a 4-D development model which has stages consisting of: define, design, develop, and disseminate. The data collection instruments used were an expert validation questionnaire, practicality questionnaire, and pretest-posttest questions. The subjects of this study were students of class XII SMAN Gogol. The results show that the assessments of material experts and media experts obtained valid criteria. In the practical aspect, the learning media are stated to be very practical to use as a support for learning from the assessment of teachers and students. In the pretest-posttest results of students, the increase in learning outcomes is at the "medium" level seen from the n-gain test scores so the "Pintar Polinomial" learning media is declared to be effectively used in learning polynomial material. It can be concluded that the "Pintar Polinomial" learning media is feasible to use in learning because it has met the criteria of validity, practicality, and effectiveness.